Pengaruh Edukasi Terhadap Pengetahuan Swamedikasi Batuk pada Anak di Kecamatan Wonosari Kabupaten Klaten Jawa Tengah - Inaratul Rizkhy Hanifah; Annisa Nur Safitri; Ika Purwidyaningrum (Fakultas Farmasi Universitas Setia Budi, 2021)
Self-medication is one way people treat a symptom of a disease without using a doctor's prescription. Knowledge of correct self-medication is needed to cure coughs without other adverse effects on the sufferer. This study aimed to determine the effect of education through online media on the level of knowledge about cough self-medication for children in Wonosari District, Klaten Regency, Central Java in 2020. This research is a quantitative study with a Quasi-Experimental research method with the technique of Two Group Pre-Test-Post-Test Control Group Design. The population in this study were parents who had children in Wonosari District, Klaten Regency. The sample in this study amounted to 268 people. The data collection tool uses a questionnaire that has been tested for validity and reliability. The results showed that the level of public knowledge when the pre-test was carried out was classified as good (41.04%), moderate (54.48%), poor (4.48%), not good (0%). The provision of education was able to increase the respondent's knowledge as indicated by the results of post-test knowledge, which were classified as good (89.55%), moderate (10.45%), not good (0%), poor (0%). The Wilcoxon test analysis obtained a p-value of 0.000 000 <α value of 0.05, which means that education through online media affects public knowledge about cough self-medication in children.